PERFORMANCE OF COWPEA (VIGNAUNGUICULATAL) VARIETIES OF MEDIUM DURATION MATURITY AT SUDAN –SAVANNA AGRO-ECOLOGICAL ZONE OF NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
These experiments were conducted in 2016 and 2017 rainy seasons at the teaching and research farm of the Federal University Dutsin-Ma(Longitude 07029'29" E and Latitude 12027'18" N) The objectives of the research were to evaluate the productivity of twenty four varieties of cowpea sourced from International Institute of Tropical Agriculture (IITA) and to recommend the most productive varieties to the community. The experiments consisted of twenty four (24) varieties of cowpea of medium duration maturity, they included IT07K-274-2-9, IT07K-269-1, IT10K-832-1, IT10K-832-2, IT10K-835-10, IT10K-180-11, IT08K-193-14, IT110-16-71, IT110-21-143, IRS-09-1009-7, IRS-09-1106-4, IAR- 07- 1050, IAR-07-1032-1, IAR-07-1042-1, IAR-07-1058 UAM-1046-6-1, UAM-1051-1, UAM14-154-10-2, UAM14-155-10-3, UAM14-145-4-3, IT07K-297-13, IT08K-150-24, IT08K-150-12 and IT07K-292-10 as check. These twenty four varieties were randomized and laid out in a randomized complete block design (RCBD) and replicated three times. The collected data was subjected to statistical analysis. IT07K-274-2-9, IT09K-832-1, IRS-09-1009-7, IAR 1032-1, IAR-07-1050, IT10K-835—10, IT10K-193-14, IT09K-269-1 and UAM-1046-6-1recorded significantly (P
Keywords: cowpeas, performance, varieties, yield